Integrity: What it is and Why it is Important. (18th January 2018) - Huberts, L. W. J. C.
Abstract : "Integrity" has become a concept and topic with more prominence in research on government and governance, as well as in actual policy making at all levels. This contribution will address basic questions about integrity. What views and interpretations of "integrity" can be distinguished? Eight different views will be summarized, with additional reflection on the underlying basics of an integrity "approach" and on its relationship with concepts/views with "ethics" or "corruption" or "good governance" in the center. It will be concluded that integrity is a crucial concept for an understanding of governance. Not as an alternative for "ethics theory and approaches" but to be embedded in existent "approaches" and theory development. In that sense it belongs on the agenda for further progress in these fields of study, in particular in empirical research on the actual significance of integrity and ethics in governance ("empirical turn").